2015
DOI: 10.1074/mcp.m115.054031
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin Alters the Proteome of High Density Lipoproteins: Generation of alpha-1-antitrypsin Enriched Particles with Anti-inflammatory Properties*

Abstract: Statins lower plasma cholesterol by as much as 50%, thus reducing future cardiovascular events. However, the physiological effects of statins are diverse and not all are related to low density lipoprotein cholesterol (LDL-C) lowering. We performed a small clinical pilot study to assess the impact of statins on lipoprotein-associated proteins in healthy individuals (n = 10) with normal LDL-C (<130 mg/ dL), who were treated with rosuvastatin (20 mg/day) for 28 days. Proteomic analysis of size-exclusion chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
49
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 41 publications
4
49
2
1
Order By: Relevance
“…Recent studies have provided evidence for an interaction between AAT and lipoproteins, including both LDL (37) and HDL (38,39). Binding of AAT to reconstituted HDL reduced the inhibitory capacity of AAT toward NE (39), and a similar effect was seen in our study when lipoproteins were removed from the plasma matrix.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Recent studies have provided evidence for an interaction between AAT and lipoproteins, including both LDL (37) and HDL (38,39). Binding of AAT to reconstituted HDL reduced the inhibitory capacity of AAT toward NE (39), and a similar effect was seen in our study when lipoproteins were removed from the plasma matrix.…”
Section: Discussionsupporting
confidence: 72%
“…Binding of AAT to reconstituted HDL reduced the inhibitory capacity of AAT toward NE (39), and a similar effect was seen in our study when lipoproteins were removed from the plasma matrix. Moreover, we noticed that allele-specific differences of the dissociation constant disappeared, supporting our hypothesis of an altered interaction of M1(V213) AAT with lipoproteins in the complex plasma environment.…”
Section: Discussionsupporting
confidence: 65%
“…Long‐term statin exposure increases HDL's anti‐inflammatory and antioxidant capacity 23, 26, 38. In our study, the strength of the association between high HDL cholesterol concentration and decreased AKI was greatest among patients receiving long‐term statin therapy, was related to dose of long‐term preoperative statin, and was enhanced among patients randomized to receive perioperative atorvastatin.…”
Section: Discussionmentioning
confidence: 48%
“…Recently, statins have been found to exert biological effects on osteoporosis, inflammation and other diseases in addition to their hypocholesterolemic activities [29][30][31]. Furthermore, several studies have shown that treatment with statins can reduce reproductive damage induced by hypercholesterolemia, however, the mechanisms by which obesity impairs spermatogenic function and how statins help recover from obesity-induced damage in the testes, sperm parameters, sex hormones, and metabolism is still unclear [32].…”
Section: Discussionmentioning
confidence: 99%